Korelasi Multivariat Antara Kepemimpinan Transformasional dengan Perilaku Peran Extra Dan Komitmen Organisasi pada PT. Sri Isman (Sritex) Sukoharjo Solo - Bambang Setyadarma; Bambang Sukarsono (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2014)
The objective of this research is to investigate the multivariate correlation between the transformational leadership with extra role behavior and the commitment of organization in PT. Sritex, Sukoharjo Solo. The samples used in this research are 140 permanent employees of PT. Sritex Sukoharjo Solo as the participant. The samples are taken using non probability sampling technique (judgment sampling method). The research’s implication explains that transformational leadership correlated with multivariate of extra role behavior and the commitment of organization. This research used three multivariate models. The 3th(third) model of multivariate indicates that the variant of extra role behavior and the commitment of organization are correlate each other, it is explained by the charisma of transformational leadership, the inspiration of transformational leadership, the intellectual stimulation of transformational leadership and the personal consideration of transformational leadership that amounted to 96,2 percent. This fact shows the evidence that the style of transformational leadership is highly favored by the employee at PT. Sri Isman (Sritex) Sukoharjo Solo for enhancing competence (competitiveness) of the quality of cloth that is produced by the fabrication Sritex today, in order to serve a segment of the market retail cloth the area of the European union and the united states in accordance with operational standard production ISO 2010.